Capacity and absorption rate of tertiary and hindered amines blended with piperazine for CO2 capture. (22nd November 2016) - Du, Yang; Yuan, Ye; Rochelle, Gary T.
Abstract: Aqueous piperazine (PZ) blended with a tertiary or hindered amine combines the high CO2 capacity of the tertiary or hindered amine with the fast rate of PZ. For flue gas CO2 capture, the optimum pKa (that which offers the highest CO2 cyclic capacity) of a mono-tertiary amine blended with PZ is 9.1. A generic Aspen Plus® model for PZ/tertiary amine was developed to predict the CO2 vapor-liquid-equilibrium (VLE) from the pKa of the tertiary amine. The polarity of the tertiary amine also affects the CO2 solubility of the PZ/tertiary amine. Hindered amines that form little carbamate show similar CO2 VLE to tertiary amines with the same pKa, when blended with PZ. The CO2 absorption rate of most 2.5 m PZ/2.5 m tertiary amines was slightly slower than 2.5 m PZ, probably due to the higher viscosity of the blends. Highlights: 21 tertiary and hindered amines blended with PZ have been studied for CO2 capture. The optimum pKa of a tertiary amine blended with PZ is around 9.1. A generic Aspen Plus® model for PZ/tertiary amine has been developed. Hindered amines show similar CO2 VLE to tertiary amines in PZ blends. PZ/2E-4 M-IMI and PZ/HMPD are promising solvents for CO2 capture from flue gas.